Substantion of Judicial Decisions and Overcoming the Free Motivated Conviction - Freitas, Gabriela Oliveira (2016)
This paper analyzes the substantiation of judicial decisions, from a perspective of democratic processuality, seeking to define the import of the provision contained in art. 93, IX of the Federal Constitution, related its forecast in the new text Code of Civil Procedure. From the comments made about such an institute, intend to investigate if still prevalent in the Brazilian legal system the free motivated conviction principle. For the present study, it’s used the literature and the deductive method, starting from a macro perspective for micro analytical view on the subject under study.